Association between fragmented QRS complexes and left-ventricular dysfunction in anabolic androgenic steroid users. Issue 3 (3rd May 2020) - Kaya, Ülker; Eren, Hayati; Öcal, Lütfi; İnanır, Mehmet; Balaban, İsmail
Abstract: Background: Anabolic androgen steroid (AS) use has adverse effects on left ventricular functions, such as fibrosis development. Fragmented QRS is an important marker of myocardial fibrosis, while speckle-tracking echocardiographyis a method used to show subclinical left ventricle dysfunction. In this study, we examined the the ability of fQRS + to detect left ventricle fibrosis by speckle tracking echocardiography (STE) in AS users. Methods: The study included a total of 181 healthy athletes. Athletes were divided into two groups as AS users ( n  = 89) and non-AS users ( n  = 92). Then, athletes using AS were divided into two groups as fQRS+ ( n  = 52) and fQRS− ( n  = 37). In both groups, the arithmetic mean of three images was used to obtain the left ventricle global longitudinal strain (LV-GLS). The E/SRe ratio was also calculated and analysed. Results: There were significant differences between the AS users and non-AS users in terms of, E/SRe (55.7 ± 17.9 vs 50.3 ± 14.8; p  = 0.015), LV-GLS (23.1 ± 1.9 vs 24.0 ± 1.7; p  = 0.001), and fQRS (18.5% vs 6%; p  = 0.005). When subgroup analysis was performed, both LV-GLS and E/SRivr were found to be poor in the fQRS + group. When multiple linear regression analysis was performed, we determined fQRS as an independent predictor for LV-GLS and E/SRivr ratio. Conclusion: In conclusion, our study demonstrated that fQRS is a parameter that can beused to determine left ventricle subclinical systolic and diastolic dysfunction in AS users. It can be used for cessation of drug use, especially in long-term use.